Lipase-catalyzed synthesis of glucose-6-O-hexanoate in deep eutectic solvents - Pöhnlein, Martin; Ulrich, Jonas; Kirschhöfer, Frank; Nusser, Michael; Muhle-Goll, Claudia; Kannengiesser, Bastian; Brenner-Weiß, Gerald; Luy, Burkhard; Liese, Andreas; Syldatk, Christoph; Hausmann, Rudolf (European Journal of Lipid Science and Technology, 2015)
Enzymatic synthesis of sugar fatty acid esters in organic solvents is a well-described procedure to synthesize glycolipids. This study aims at replacing these solvents with deep eutectic solvents (DES), a group of solvents that gained more and more interest during the last years, since they can be easily produced from non-toxic resources. Enzymatic glycolipid synthesis in deep eutectic solvents was investigated, employing Candida antarctica lipase B (Novozyme 435) in various deep eutectic solvents. A successful lipase-catalyzed synthesis of glucose fatty acid esters gave proof of this concept, while using the two deep eutectic solvents consisting of choline chloride and urea (CC : U) and choline chloride and glucose (CC : Glc). Additionally the DES consisting of choline chloride and glucose was observed to act as solvent and substrate for the synthesis at the same time. 1 Practical applications Glycolipids find applications in many everyday products like cosmetic and pharmaceutical formulations, food and classic cleaning products, utilizing their good detergent or emulsification properties. Glycolipids can, among other routes, be synthesized via lipase-catalyzed reactions, which are often carried out in organic solvents. By replacing these organic solvents with more ecologically friendly solvents like deep eutectic solvents, the reaction might be improved and the amount of waste produced could be reduced. The lipase-catalyzed synthesis of glucose-6-O-hexanoate employing glucose and vinyl hexanoate in different deep eutectic solvents was demonstrated within the manuscript.